Contractual complexity, governance and organisational form in alliances. (19th January 2011) - Schweitzer, Jochen; Gudergan, Siegfried P.
Contracting and governance related issues are critical for the success of alliances. In this paper, we provide a theoretical framework to describe the role of the contractual complexity of alliance agreements for the governance and organisational form of alliances. We suggest control theory to explain how the goal incongruence and performance ambiguity among collaborating partners, in conjunction with the complexity of their contractual agreements, affect the organisational form of alliances that can be characterised as bureaucracy, market, clan, or adhocracy. Our framework implies that managers who review and control contractual complexity, goal incongruence, and performance ambiguity, will be able to identify and employ governance for their alliances that better supports their firm's strategic intentions.